Effect of intercropping systems on phenology and yield of pigeonpea (Cajanus cajan L.), pearlmillet (Pennisetum glaucum L.) and greengram (Vigna radiata) under western Haryana condition - Barod, Niranjan Kumar; Kumar, Satish; Baghel, Manmohan (Annals of Agricultural Research, 2016)
The investigation entitled "Response of nitrogen application in wheat succeeding pigeonpeaintercropped with pearlmillet and greengram" was carried out at the research farm of ChaudharyCharan Singh Haryana Agricultural University, Hisar during kharif and rabi seasons of 2011-12 and2012-13. Wheat crop was taken during rabi seasons. It comprised of 12 treatments in kharif and 3treatments in rabi and the set of treatments was replicated thrice in randomized block design inkharif and split-plot in rabi season. Different intercropping systems failed to produce significantvariation in days taken to emergence, 50% flowering, 50% pod formation and physiological maturityin pigeonpea, pearlmillet and greengram. The phenology viz. days taken to emergence, 50% headingand physiological maturity were not influenced significantly during both years in pearlmillet anddays taken to emergence, 50% flowering, 50% pod formation and physiological maturity were notinfluenced significantly by different intercropping systems in greengram. Whereas, grain, strawand biological yield were the highest in sole crop i.e. pigeonpea (1983 and 2059, 2059 and 5947 and7777 and 8006 kg ha–1) respectively, pearlmillet (2122 and 2218, 5999 and 6200 and 8121 and 8418 kgha–1) respectively, and greengram (1319 and 1402, 3925 and 4175 and 5244 and 5576 kg ha–1)respectively during 2011 and 2012 crop seasons.